Experimental research on the effect caused by effective stress change in injection production capacity of carbonate reservoir - Gao, Xinping; Yang, Jian; Han, Huifen; Peng, Junliang; Peng, Huan; Yang, Zhifan (Frontiers in Earth Science, 2023)
The effective stress of the reservoir rock in the underground gas storage (UGS) changes with the multi cycle injection and production, which changes the physical characteristics of the reservoir and affects the injection production capacity of the UGS. Taking carbonate fracture-pore type gas storage as the research object, combined with the actual production of UGS, establish a set of experimental evaluation methods based on production characteristics; Core damage evaluator, overburden pressure porosimeter and scanning electron microscope are used to carry out experimental research on the impact of effective stress change on injection production capacity, quantitative analysis of reservoir internal characteristics, multi cycle injection and production and effect of effective stress action time on injection-production capacity. The results show, the experimental method established based on the actual production characteristics of the UGS, simulation of multi cycle injection and production by forward and reverse displacement, simulation of effective stress change under constant confining pressure and variable internal pressure, the experimental evaluation of the injection production capacity of the simulation multi cycle injection and production of the UGS is realized; The change of effective stress makes the reservoir seepage characteristics worse and the reservoir space smaller, injection-production coefficient (Szc) is positively correlated with the internal characteristic value of the reservoir, the larger the internal characteristic value of the reservoir, the higher Szc, and the better the injection production capacity; The injection production capacity of the UGS reservoir deteriorates with the increase of the injection production cycle, in the 4th injection production cycle, the injection production capacity of the UGS changes from moderately strong to moderately weak; The damage of effective stress to the injection production capacity of UGS mainly occurs in the initial stage of injection production, and the damage tends to be stable with the progress of injection production. The conclusion is that the change of effective stress in carbonate fracture-pore type gas storage makes the injection-production capacity of the reservoir worse, it is proposed to carry out reservoir reconstruction before the UGS is put into operation, and expand the capacity of the gas storage after the completion of the 3rd injection and production cycle, which can effectively offset the impact of the decline of injection production capacity of the UGS and play the role of reservoir protection, it provides a constructive idea for improving the operation efficiency of the UGS.